Delayed vaccination and its predictors among children under 2 years in India: Insights from the national family health survey–4. Issue 17 (17th April 2019) - Choudhary, Tarun Shankar; Reddy, N. Samarasimha; Apte, Aditi; Sinha, Bireshwar; Roy, Sudipto; Nair, Nayana P.; Sindhu, Kulandaipalayam Natarajan; Patil, Rutuja; Upadhyay, Ravi Prakash; Chowdhury, Ranadip
Abstract: Objective: Delayed vaccination increases the susceptibility window for vaccine preventable diseases. Our analysis estimates the proportion of children between 10 and 23 months of age with delayed vaccination in India and the associated socio-demographic, maternal and child related factors. Methods: We used individual level data from the National Family and Health Survey 4, conducted in 2015–2016. The primary outcome of the study was delayed vaccination for BCG, DPT- 1st dose and Measles. Delayed vaccination for each vaccine was defined as administration of the vaccine dose after 28 days of the minimum recommended age, as per the national immunization schedule in India. We estimated the proportion of children with delayed vaccination for each vaccine and used multivariable logistic regression to explore associated factors. Findings: In the current analysis, 23.1%, 29.3% and 34.8% of children aged 10 to 23 months had delayed vaccination for BCG, DPT-1st dose and Measles respectively. Children from Muslim families (aOR 1.36 for BCG; aOR 1.45 for DPT-1; aOR 1.26 for Measles); birth weight < 2000 g (aOR 2.33 for BCG; aOR 1.53 for DPT-1; aOR 1.36 for Measles) had higher odds of delayed vaccination. Lower maternal education and belonging to a family from lower wealth quintile had higher odds of delayed vaccination. Children of mothers who had tetanus toxoid immunization during pregnancy had lower odds of delayed vaccination (aOR 0.69 for BCG; aOR 0.76 for DPT-1; aOR 0.78 for Measles). Conclusion: The proportion of children with delayed vaccination is high in India. Vaccine timeliness should be a core indicator of the immunization program with greater focus on groups with higher chances of delayed vaccination i.e. home birth, low birth weight new-borns, poorer households, children of mothers with lower education and children from Muslim families.